Difficult Denture Birds: An Easy Psychological Assessment - Yarlagadda, Siva Kiran Babu; Srinath, HP; Prasad, K Sitaram; Reddy, A Venkat (Journal of Orofacial Research, 2013)
Individuals who present uncommon and abnormal denture problems require unusual and resourceful treatment. Because of the extreme complexity of their systemic illness, physical,psychogenic abnormalities, anatomic abnormalities and neurological disorders, these are the difficult denture birds. This article mainly describes about difficult denture birds and theirmanagement.